GOOD AND BAD STANDARDS BASED ON MORAL TEACHINGS, MORALS AND ETHICS - Abdul Wahab Syakhrani; Fakhriana Hayati (ADISAM Publisher, 2022)
The good and bad standard is the Al-Qur'an hadith, where there is a concept of religion, that is where there are good and bad standards, in learning there are fardhu'ain, fardhu kifayah, sunnah, things related to aqidah, fiqh, tasawuf, that is must. According to Islamic teachings, the determination of good and evil must be based on the guidance of the Al-Qur'an and Al-Hadith. If we pay attention to the Qur'an and hadith, there are many terms that refer to good, and there are also terms that refer to bad. Among the terms that refer to good, for example hasanah, thoyyibah, khairoh, karimah, mahmudah, azizah and birr.